Detection of Leukemia Using Machine Learning Algorithms. Issue 1 (May 2021) - Jayavikash, K P; Gopinath, P; Nandheeswaran, U; Sivabalan, R; Divya Bharathi, T
Abstract: Detection of disorders of Blood usually include visual inspection through a microscope. This may help to classify various conditions related to human blood. The paper details about evolving a system that could help in diagnosis and detection of Leukemia at an early stage. Only then controlling and prevention can be done. The proposed system focuses on White Blood Cells as they are the affected ones in case of Leukemia. The affected cells differ in shape and color features, which are used as classifier inputs.